Early diagnostics of gingivitis using infrared spectroscopy of biological fluids of the oral cavity - O. A. Smetanina; L. N. Kazarina; A. S. Gordetsov; O. V. Krasnikova (LLC "Endo Press", 2019)
For the time being, there are many laboratory and clinical techniques, which are widely used for the diagnosis of gingivitis, but the exact method of prognosis and early diagnosis of gingivitis in children hasn't been revealed yet. Among the new diagnostic techniques being under development, is infrared spectroscopy, which is widely used in various fields of medicine and which has also found its application in dentistry is of great interest. In the article the materials of studies on the effectiveness of the use of the infrared spectroscopy method of oral biological fluids in children for early diagnostics of chronic catarrhal gingivitis are presented. Using this technique it is possible to predict the appearance of gingivitis in children at an early, pre-clinical stage, which is confirmed by our results. After the treatment the positive dynamics of the clinical state of periodontal tissues in patients are observed. Infrared spectroscopy is a non-invasive, inexpensive, easy to perform and highly informative method and can be used as an alternative way not only in the diagnosis of a periodontal disease, but also in the study of early forms of manifestations of the disease to assess the long-term results of treatment.